Ethnobotanical study of medicinal plant used by Dusun Liwan Community along Bukit Manggis road Papar, Sabah / Chernietika Madius - Madius, Chernietika (Faculty of Applied Sciences, 2017)
Ethnobotany is the study of plants related to its uses by people in a community. This study emphasizes more on the medicinal plants used by Dusun Liwan community along Bukit Manggis road Papar, Sabah. There are seven informants with 63 species of medicinal plants cited and documented through interview session and semi structured questionnaire. Medicinal plants data are documented for their life form, part used, preparation method, tradition used and mode of administration. Each medicinal plants are classified based on their phylum, class, sub-class, order, family, genus and species. Major ethnobotanical techniques are used in this study which involved the field investigation, interview, collecting samples, pressing, drying, mounting, identification, classification, constructing dichotomous key and calculating medicinal plant’s use value index. The samples that collected can treat 21 types of ailments: skin infection, stomach’s problem, blood’s problem, cancer, fever, jaundice, pyretic, cough, sore throat, diabetes, afterbirth, flatulence, antiaging, lumbago, headache, asthma, small pox, mouth infection, sore eyes, heart attack, tooth pain, acne, migraine, and osteoporosis. The plants are classified into Kingdom of Plantae, 2 Phylum, 3 Class, 10 Sub-class, 27 Order, 36 Family, 56 Genus and 62 Species. The use value index was employed to determine the relative importance of all medicinal plants with its other use category such as for construction, food and ornamental purpose. In this study, there were 16 species in the medium range of 0.5 to 1 while 47 species were in high range which was higher than 1. Therefore, this study will serve as a reference for the future. The indigenous knowledge of these medicinal plants used by Dusun Liwan community along the Bukit Manggis road Papar, Sabah also was preserved through this study of ethnobotany.